Improving Young Learners Vocabulary by Using Digital Technology - Triesye A Laloan (English Education Postgraduate Program, Universitas Negeri Manado, 2022)
This writing aims at describing the possible ways in increasing young learners vocabulary Vocabulary is a very important part of language When we learn a language like English we learn the words in the language Vocabulary is needed to master the four skills of English Through vocabulary we convey our thoughts emotions and efficiency Although it is often hampered by lack of grammar or grammatical errors in its use But in communication it does not become an obstacle as long as the speaking partner understands The methodology of this research is library research Using previous research as the basis of what is being researched Understanding the important things to take as material from this research To improve young leaners vocabularies by technology need guidance between parents teacher and school environment As a form of response to technological developments stakeholders are Education sector conducts teacher training teacher education and teacher professions developing Vocabulary not only mastered by young leaners but there are others too When they have oral or written communication language they use vocabulary to express their thoughts and ideas Although in reading one must understand the meaning of words write on the text Of course master English vocabulary takes time and process < em>< p>